2016
DOI: 10.1038/ncomms10394
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous liquid crystal and ferromagnetic ordering of colloidal magnetic nanoplates

Abstract: Ferrofluids are familiar as colloidal suspensions of ferromagnetic nanoparticles in aqueous or organic solvents. The dispersed particles are randomly oriented but their moments become aligned if a magnetic field is applied, producing a variety of exotic and useful magnetomechanical effects. A longstanding interest and challenge has been to make such suspensions macroscopically ferromagnetic, that is having uniform magnetic alignment in the absence of a field. Here we report a fluid suspension of magnetic nanop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 39 publications
3
71
0
2
Order By: Relevance
“…This is often achieved by coating the surface with monomolecular organic materials, surfactants (stabiliser), or ligands. For instance, oleic acid, 7,10,17,20,21,[24][25][26][27] selenium docosane 28 and dodecylbenzenesulphonic acid 29,30 have been widely utilized for the coating of NPs.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…This is often achieved by coating the surface with monomolecular organic materials, surfactants (stabiliser), or ligands. For instance, oleic acid, 7,10,17,20,21,[24][25][26][27] selenium docosane 28 and dodecylbenzenesulphonic acid 29,30 have been widely utilized for the coating of NPs.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…Covering the surface of nanoparticles with properly designed LC ligands yields systems able to form nematic, smectic, and complex 3D structures . It was shown that the melting of LC affects the plasmonic properties of the material (i.e., causes the shift of SPR wavelength), therefore significant effort was directed at controlling the organization of nanoparticles by temperature .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the large magnetocrystalline anisotropy, high Curie temperature T c and saturation magnetization M s , barium hexaferrites [BaFe 12 O 19 , BaM] are of great interest for magnetic recording, microwave magnetic devices, and permanent magnets123. Many schemes34567 have been attempted in the past few decades to improve the intrinsic magnetic properties of barium hexaferrites.…”
mentioning
confidence: 99%